HYBRID PROBLEM BASED TEACHING AS AN ATTEMPT TO IMPROVE LEARNING OUTCOMES - Ahmad, Madiha; Khan, Huma Saeed; Hasan, Shahid; Asim, Muhammad (Pakistan Journal of Physiology, 2015)
Discussions and debates over the merits and de-merits of a single, ideal system of teaching and learning have ranged over decades. Objective of this study was to analyse the effectiveness of hybrid problem based learning to improve learning in under graduate students. Methods: Two sessions of first year MBBS undergraduate students were compared. Lecture based teaching and hybrid problem based teaching on the same topic were done. Both were evaluated at the end of the term by a pre-test and a full term exam. Results: The overall marks obtained by students of hybrid problem based learning session in pre-test exam were significantly higher when compared to the lecture based session. When the marks of pre-test were categorized below 50%, between 50 65%, 66–80% and above 80% and then compared, they were significant (p<0.001). Students of hybrid problem based learning session obtaining 66–80% marks were 35.9%, and 7% obtained marks above 80%, while in the other session 5.7% had 66–80% marks and none had >80%. End-of-term exams results showed students of lecture based session having mean marks better than the others. Conclusion: Problem based learning has an advantage over lecture based learning enabling better retention of basic concepts and its improved application in clinical settings.